Optimalisasi Media Sosial untuk Meningkatkan Pemasaran UMKM Di Era Digital - Habibullah Habibullah; Diana Airawaty (Jurnal Pelayanan Masyarakat, 2024)
The digital era has changed consumer behavior and the way of doing business, especially for Micro, Small, and Medium Enterprises (MSMEs). This article discusses social media optimization strategies to improve MSME marketing. By analyzing the development of social media and digital consumer behavior, this article presents practical recommendations for MSMEs to increase their awareness, increase sales, and build customer loyalty. The approach used in this study is to conduct training and workshops involving professionals in the field of digital marketing. This study shows that social media optimization can be the key to increasing the competitiveness and success of MSMEs in the digital era.